PENGARUH EFIKASI DIRI DAN LINGKUNGAN SEKOLAH TERHADAP KECURANGAN AKADEMIK PADA MATA PELAJARAN IPS TERPADU - Ida Puspitasari; Agus Priyono; Udik Yudiono (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2018)
This study aims to analyze effect of self efficacy and school environment on fraud academic on the subjects of IPS Terpadu students of class VII SMP Negeri 3 Kepanjen. This research uses quantitative approach, this type of research is ex post facto. Statistical data of the study using multiple linear regression. The population in this research is all student of class VII SMP Negeri 3 Kepanjen amounted to 320 students, research sampling technique using proportional random sampling number of 60 students. The results of the research are: (1) Negative and significant influence between self efficacy and school environment on fraud academic on IPS Terpadu subjects class VII SMP Negeri 3 Kepanjen, 2) The negative and significant effect of self efficacy on fraud academic on the subjects of IPS Terpadu VII grade students of SMP Negeri 3 Kepanjen, 3) Negative effects and significant of school environment against fraud academic on the subjects of Social Studies IPS Integrated grade VII SMP Negeri 3 Kepanjen.